2015
DOI: 10.1093/jac/dkv186
|View full text |Cite
|
Sign up to set email alerts
|

WGS accurately predicts antimicrobial resistance inEscherichia coli

Abstract: WGS can provide comprehensive resistance genotypes and is capable of accurately predicting resistance phenotypes, making it a valuable tool for surveillance. Moreover, the data presented here showing the ability to accurately predict resistance suggest that WGS may be used as a screening tool in selecting anti-infective therapy, especially as costs drop and methods improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
166
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(184 citation statements)
references
References 31 publications
17
166
1
Order By: Relevance
“…The same four genes were detected in chloramphenicol-resistant E. coli strains in a previous study, which also reported floR as the most prevalent gene (33).…”
Section: Ere(b) Erm(b) Mph(a) and Mph(b) In 23 Isolates The Ersupporting
confidence: 77%
“…The same four genes were detected in chloramphenicol-resistant E. coli strains in a previous study, which also reported floR as the most prevalent gene (33).…”
Section: Ere(b) Erm(b) Mph(a) and Mph(b) In 23 Isolates The Ersupporting
confidence: 77%
“…DNA extractions were performed using Qiagen DNeasy blood and tissue kits, with library preparations performed using either Illumina v2 or v3 reagent kits with paired-end reads. Each isolate was subjected to whole-genome sequencing on the MiSeq platform, as described previously, with minimum N50 values of 30 kb and 20-fold coverage required for each assembled genome (9).…”
Section: Methodsmentioning
confidence: 99%
“…For most bacteria, the evidence for using WGS to infer antimicrobial susceptibility data is sparse, although some studies have shown a high correlation between resistance phenotypes and the presence of resistance genes or resistance-associated mutations. This agreement has been best demonstrated with enteric bacteria, including Escherichia coli, Campylobacter spp., and nontyphoidal Salmonella (8)(9)(10)(11)(12). In addition, other DNAbased methods have been used to detect resistance determinants and even guide therapy for infections caused by Mycobacterium tuberculosis, Staphylococcus aureus, HIV, and other pathogens (13)(14)(15).…”
mentioning
confidence: 99%
“…Previously reported antibiotic resistance genes were downloaded from GenBank to a local database that contained 2,546 resistance genes from a number of bacterial sources, with gene variants representing resistance to all major antimicrobial classes (12). Additional databases published previously were used as references (13,14).…”
Section: Antimicrobial Susceptibility Testing (Ast)mentioning
confidence: 99%